Analisis Keputusan Manajerial Sistem Profit Loss Sharing Terhadap Tingkat NPF Bank Umum Syariah di Indonesia - Fajar, Maulana; Yuliana, Novita; Ratnawati, Dwi Puji; Kusuma, Triana Hasty (Universitas Muhammadiyah Magelang, 2024)
This research was conducted with the aim of analyzing the relevance between the PLS (Profit and Loss Sharing) financing system, which includes mudharabah and musyarakah, and the value of non-performing financing (NPF). The analytical method applied is quantitative analysis using panel data and the Eviews 12 application program. The research data is secondary data sourced from the annual reports of Islamic banks in Indonesia, published from 2012 to 2023. The results of the analysis conclude that mudharabah financing has a significant negative impact on NPF, while musyarakah financing has a significant positive impact on NPF. The analysis also shows that the amount of mudharabah financing is much smaller compared to musyarakah financing, indicating that the potential risk of musyarakah financing is much higher than that of mudharabah financing.